2006
DOI: 10.1111/j.1600-065x.2006.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune privilege and HIV‐1 persistence in the CNS

Abstract: Human immunodeficiency virus-1 (HIV-1) neuroinvasion occurs early (during period of initial viremia), leading to infection of a limited amount of susceptible cells with low CD4 expression. Protective cellular and humoral immunity eliminate and suppress viral replication relatively quickly due to peripheral immune responses and the low level of initial central nervous system (CNS) infection. Upregulation of the brain protective mechanisms against lymphocyte entry and survival (related to immune privilege) helps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
44
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 168 publications
(192 reference statements)
0
44
0
Order By: Relevance
“…38 Our previous results pointed to RhoK as a potential kinase of TJ proteins, activation of which might be the molecular mechanism mediating BBB dysfunction in neuroinflammation. 20 This study demonstrated that RhoK indeed phosphorylated cytoplasmic domains in CLD5 and OCC at specific sites.…”
Section: Discussionmentioning
confidence: 99%
“…38 Our previous results pointed to RhoK as a potential kinase of TJ proteins, activation of which might be the molecular mechanism mediating BBB dysfunction in neuroinflammation. 20 This study demonstrated that RhoK indeed phosphorylated cytoplasmic domains in CLD5 and OCC at specific sites.…”
Section: Discussionmentioning
confidence: 99%
“…These include tight junctions and low levels of adhesion molecule expression by capillary endothelial cells; neuronal expression of CD200, which reduces microglial cell activation; local production of neurotrophins; and transforming growth factor ␤ secretion by astrocytes and meningeal cells (31). In addition, the brain is a potential anatomic reservoir for HIV-1 replication (24,63). While inflammatory and innate immune mechanisms that involve trafficking of monocyte/macrophages are central to the pathogenesis of HIV-associated dementia (28,(84)(85)(86), viral replication also plays a major role, with viral proteins gp120 (4,5,20,34) and tat (12,49,57,60) being directly neurotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…HIV enters the central nervous system (CNS) soon after initial infection, during the initial period of systemic viremia (Palmer et al 1994;Persidsky and Poluektova 2006;Resnick et al 1985). The predominant mechanism of entry is via macrophages/monocytes (Gendelman et al 1989).…”
mentioning
confidence: 99%
“…However, the brain's own defenses, including an influx of CD8+ cells, typically restrict productive HIV infection until a second wave of infected monocytes crosses the blood-brain barrier (Persidsky and Poluektova 2006). This second wave typically occurs in advanced disease and may be triggered by advanced immunosuppression outside the CNS, as marked by a decline in CD4+ cells and breakdown in the ability of the immune system to control viral replication, or by an increase in chemoattractant substances and adhesion factors in the brain (Maslin et al 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation